Design of an empirical process model and algorithm for the Tungsten Inert Gas wire+arc additive manufacture of TI-6AL-4V components - Martina, Filomeno; Williams, Stewart W.; Colegrove, Paul A. (University of Texas, 2013)
In the wire+arc additive manufacture process parameters can be varied to achieve a wide range of deposit widths, as well as layer heights. Pulsed Tungsten Inert Gas was chosen as the deposition process. A working envelope was developed, which ensures unfeasible parameters combinations are excluded from the algorithm. Thanks to an extensive use of a statistically designed experiment, it was possible to produce process equations through linear regression, for both wall width and layer height. These equations are extremely useful for automating the process and reducing the buy-to-fly ratio. For a given layer height process parameters can be selected to achieve the required layer width while maximising productivity.